MODUL BERBASIS PBL UNTUK MEMFASILITASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS KONTEN BARISAN DAN DERET GEOMETRI - Ilyas Mulama Hartanta; Sakur; Armis (Universitas Teknokrat Indonesia, 2026)
The background of this study stems from the inadequacy of students' mathematical problem-solving competencies alongside the scarcity of instructional materials aligned with the Merdeka Curriculum. Teacher-dominated instruction deprives learners of opportunities for autonomous exploration. Accordingly, this study intends to construct a PBL-anchored instructional package covering geometric sequences and series for phase F that is both valid and practical. An R&D approach employing the 4-D framework was adopted, encompassing define, design, develop, and disseminate stages. Product trials took place at SMKN Pertanian Terpadu Pekanbaru. Three assessors rated validity as